RUSIAN ARCHITECTURE OF THE 10TH–13th CENTURIES. CATALOG OF MONUMENTS. GALICIA (EXCERPT FROM THE AUTHOR’S MONOGRAPH) - RAPPOPORT, Pavlo (Halych. Scientific work collection, 2018)
This publication is a part of the catalog of monuments of ancient monumental architecture of the pre(Mongol period of the 10th–13th centuries. It includes, in particular, 10 monuments of the stone architecture of annalistic Halych of the 12th–13th centuries, which are mostly represented by the insignificant remnants. Based on the analysis of scientific works of the Ukrainian researchers of the second half of the 19th – the first half of the 20st century, as well as the Soviet archaeologists, historians of architecture, the author attempted to reconstruct the appearance, planning, elements of the interior of the most prominent architectural monuments of princely Halych and the Galicia.